Symbolic Narratives and the Role of Meaning: Encountering Technology in South African Primary Education - Van Zyl, Izak; Sabiescu, Amalia (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2016)
This article draws on the results of a long-term, design-based research study with South African primary school teachers to discuss the role of subjectively assigned meanings and symbolisms of technology, as key factors affecting the adoption, appropriation and use of educational technology in urban poor and under-resourced environments. The paper examines how teachers’ engagements with technology are framed, conditioned, and embedded in multi-levelled “technology encounters”. These encounters give rise to meaningful representations of technology that ultimately transform both the teaching and learning process, and culminate in the emergence of “symbolic narratives”: complex assemblages of symbolisms, meanings and interpretations that arise through and therefore come to influence further technology engagements. We argue that a closer examination of teachers’ symbolic narratives can shed light on the motivations that underpin the appropriation, integration -- or conversely, rejection -- of educational technology in urban poor and under-resourced environments.
Keywords: educational informatics, information and communication technology (ICT), technology encounters, symbolic narrative, meaningful representations of technology